2023
DOI: 10.3892/br.2023.1605
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic potential of β‑galactosidase‑producing lactic acid bacteria from fermented milk and their molecular characterization

Abstract: Probiotics have attained significant interest in recent years as a result of their gut microbiome modulation and gastrointestinal health benefits. Numerous fermented foods contain lactic acid bacteria (LAB) which are considered as GRAS and probiotic bacteria. The present study aimed to investigate indigenous LAB from homemade fermented milk samples collected in remote areas of Karnataka (India), in order to isolate the most potent and well-adapted to local environmental conditions bacteria, which were then eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Lactose intolerance (LI) is a condition of inability to digest lactose with lack of deficiency of lactase (β-galactosidase) enzyme. Typical clinical symptoms include stomach discomfort and distension, borborygmi, flatulence and diarrhea that appear between 30 and 120 min after the consumption of lactose (Harrington and Mayberry, 2008;Gayathri and Vasudha, 2018;Vasudha et al, 2023b). Prevalence of LI was estimated to be 80-100% in Asian and African countries where prevalence of lactase non-persistence is reported to be quite low in Northern European countries (Ingram et al, 2009;Gayathri and Vasudha, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lactose intolerance (LI) is a condition of inability to digest lactose with lack of deficiency of lactase (β-galactosidase) enzyme. Typical clinical symptoms include stomach discomfort and distension, borborygmi, flatulence and diarrhea that appear between 30 and 120 min after the consumption of lactose (Harrington and Mayberry, 2008;Gayathri and Vasudha, 2018;Vasudha et al, 2023b). Prevalence of LI was estimated to be 80-100% in Asian and African countries where prevalence of lactase non-persistence is reported to be quite low in Northern European countries (Ingram et al, 2009;Gayathri and Vasudha, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…in between 12 and 48 hours) and slow acid producers(pH 4.6 in more than 48 hours) (Attia et al, 2001; Yi et al, 2011; Akabanda et al, 2014; Fguiri et al, 2016; Alharbi, & Alsaloom, 2021).Screening of β-galactosidase producing LABScreening of β-galactosidase producing LAB was performed by using X-gal (5bromo-4-chloro-3-indolyl-β-D-galactopyranoside) as a substrate which is, in fact, analogue of lactose and IPTG (isopropyl β-D-1 thiogalactosidase) was used as an inducer. Selected LAB were inoculated into MRS medium containing 60 μL of Xgal (20 mg/ml dissolved in DMSO) and 10 μL of IPTG solution and incubated at 37 °C/ 48 hours(Gheytanchi et al, 2010;Deng et al, 2020;Kolev et al, 2022;Vasudha et al, 2023b). Blue-colored colonies that developed during incubation were considered as β-galactosidase producing bacteria.…”
mentioning
confidence: 99%
“…Since lactic acid bacteria are widely thought to be harmless, their enzymes can be used in foods directly without being purified. [7] The primary goal of the current research is to identify new, possibly beneficial microorganism sor B-galactosidases, which convert lactose into galactose and glucose for use as carbon sources in fermentation processes. Blue hue colonies were formed by the bacteria cultured on agar media with 0.1% X-GAL.…”
Section: B-galactosidase Enzyme Production Screeningmentioning
confidence: 99%
“…Similar results were also found by Vasudha et al who found that commercial strains of Lactiplantibacillus plantarum, Limosilactobacillus fermentum, Lactiplantibacillus pentosus, and Lactiplantibacillus sp. isolated from fermented milk had high levels of the B-galactosidase enzyme [14].…”
Section: B-galactosidase Enzyme Production Screeningmentioning
confidence: 99%
See 1 more Smart Citation